Improving the implementation of NICE public health workplace guidance: an evaluation of the effectiveness of action‐planning workshops in NHS trusts in England. Issue 4 (10th March 2015) - Jones, Sarah; Sloan, David; Evans, Hannah E. R.; Williams, Sian
Abstract Rationale, aims and objectives There is evidence that health and well‐being of the National Health Service (NHS) workforce affects organizational and patient outcomes. A Cochrane review of the effectiveness of clinical audit to improve quality of care has shown great variation between studies, depending on the design and intensity of support offered. This study evaluates the effectiveness of an organizational audit methodology with (1) action‐planning workshops and follow‐up and (2) audit feedback alone, to support the implementation of the National Institute for Health and Care Excellence (NICE) workplace guidance. Methods Two rounds of audit using a self‐administered online questionnaire were conducted. An overall implementation score was devised for each trust. Following round 1, interviews were conducted with a cohort of trusts with high scores. The interviews used a theory‐based framework to identify predictors of and barriers to successful implementation. From this, the content for action‐planning workshops was devised and workshops held with lower scoring trusts. The remaining trusts received only written feedback on their audit results. Changes in the implementation score between rounds 1 and 2 were compared within and between cohorts. Results The median improvement in scores between rounds 1 and 2 was statistically significant except where baseline score was high. The improvement for trusts who received workshops was very much better than those who did not (P < 0.001). This difference remained after adjustment using stratification by baseline score (P = 0.001). Conclusions Audit, combined with action‐planning workshops and follow‐up, appears to be more effective in improving implementation of NICE workplace health and well‐being guidance than audit with feedback alone.